Notes about Quasi-Mixing Operators - Mansooreh Moosapoor; Ismail Nikoufar (Sahand Communications in Mathematical Analysis)
In this article, we introduce quasi-mixing operators and construct various examples. We prove that quasi-mixing operators exist on all finite-dimensional and infinite-dimensional  Banach spaces. We also prove that an invertible operator $T$ is quasi-mixing if and only if $T^{-1}$ is quasi-mixing. We state some sufficient conditions  under which an operator is quasi-mixing. Moreover, we prove that the direct sum of two operators is quasi-mixing if and only if any of them is quasi-mixing.